Study of the Implementation of Samarinda Mayor Regulation Number 4 of 2023 in the Kelurahan Tenun Area of Samarinda City - Yani, Ahmad; Eryani, Trisna Waty Riza; Salmon, Gregorius Agung; Wendy, Muhamad (Manunggal Halim Jaya, 2024)
This study aims to understand the implementation of Samarinda Mayor Regulation No. 4 of 2022, which amends Mayor Regulation No. 11 of 2022 regarding Guidelines for the Implementation of Community Development and Empowerment Programs (Pro-Bebaya) in Tenun Village, Samarinda Seberang District, Samarinda City. Additionally, the study analyzes the supporting and inhibiting factors related to this implementation. A qualitative descriptive research method was employed, focusing on Edward III's policy implementation model, which includes communication, resources, disposition, and bureaucratic structure. Primary data were obtained through interviews with the Head of Tenun Village as the key informant, along with other informants such as the Village Secretary, the Head of Welfare and Community Empowerment, the Chairman of the Community Group (POKMAS), and local residents. Data collection techniques included observation, interviews, and documentation, with data analysis conducted using the interactive model of Miles and Huberman. The study's findings reveal that communication in the Pro-Bebaya implementation was carried out through community meetings and socialization efforts, while human resources and supporting facilities were adequately available. However, there was a weakness in disposition, specifically the lack of involvement of the Village Community Empowerment Institution (LPM) in the selection of POKMAS members. The bureaucratic structure adhered to the established regulations. Supporting factors for the implementation included high community participation, whereas inhibiting factors were the limited time for program management and insufficient budget allocation compared to community demands. These findings highlight the need for more effective time and budget management in the implementation of the Pro-Bebaya program.